Time will tell: Working from home and job satisfaction over time - Sundermeyer, Stefanie (My University, 2025)
This article examines the short- and long-term impact of working from home on satisfaction with flexibility, feelings of loneliness, and job satisfaction and contributes towards the understanding of circumstances that determine whether working from home has positive or negative effects on job satisfaction. Theoretically, this study argues in the context of the job demands-resources model that working from home increases job satisfaction in the short-term due to increased flexibility. In the long-term, however, the positive effect of working from home on job satisfaction is expected to decrease because loneliness countervails the positive effect of flexibility. The predictions are tested using data from 16 waves of the Household, Income and Labour Dynamics in Australia Survey. Event-study regressions reveal that working from home permanently boosts satisfaction with flexibility but increases loneliness in the long run. In line with the argumentation, the results indicate that the positive effect of working from home on job satisfaction diminishes the longer employees are working from home.
German Journal of Human Resource Management
Keywords: Labour market; Lifestyle; Social engagement